The Effect of Maternal Obesity on Pregnancy Outcomes of Women with Gestational Diabetes Controlled with Diet Only, Glyburide, or Insulin - Joy, Saju; Roman, Ashley; Istwan, Niki; Rhea, Debbie; Desch, Cheryl; Stanziano, Gary; Saltzman, Daniel (American Journal of Perinatology, 2012)
Objective To examine the effect of obesity on maternal and neonatal outcomes in women diagnosed with gestational diabetes mellitus (GDM) and managed with diet only, glyburide, or insulin.Study Design Women with singleton gestations enrolled for outpatient services diagnosed with GDM and without history of pregnancy-related hypertension at enrollment or in a prior pregnancy were identified in a database. Women with GDM controlled by diet only (n = 3918), glyburide (n = 873), or insulin without prior exposure to oral hypoglycemic agents (n = 2229) were included. Pregnancy outcomes were compared for obese versus nonobese women within each treatment group and also compared across treatment groups within the obese and nonobese populations.Results Within each treatment group, obesity was associated with higher rates of cesarean delivery, pregnancy-related hypertension, macrosomia, and hyperbilirubinemia (all p < 0.05). Higher rates of pregnancy-related hypertension and hyperbilirubinemia were observed in women receiving glyburide.Conclusion Obesity adversely affects pregnancy outcome in women with GDM. Higher rates of pregnancy-related hypertension and hyperbilirubinemia were observed in pregnant women receiving glyburide.
Keywords: gestational diabetes; glyburide; obesity